2023
DOI: 10.3892/etm.2023.11865
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and effect evaluation of a stress cardiomyopathy mouse model induced by different doses of isoprenaline

Abstract: The optimum dose of isoprenaline (ISO) required to induce stress cardiomyopathy (SC) in mice is not known. The present study aimed to investigate the dose-response association and determine the optimum dose of ISO to establish a high-morbidity/low-mortality SC mouse model to simulate the clinical symptoms of SC. A total of 72 6-week-old wild-type female mice (C57BL/6) were randomly divided into control mice administered normal saline and mice treated with increasing ISO concentrations (5, 10, 25, 50 and 100 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
(55 reference statements)
1
1
0
Order By: Relevance
“…However, for the study to be clinically applicable, it is crucial that global cardiac function, when used as an outcome measure, be evaluated in the context of a TS phenotype. The impact of stress inducing a reduced global systolic function, in the absence of RWMA, appears to be a recurring finding observed by us and others ( 8 , 10 , 72 ). Thus, regions with wall motion abnormalities can be associated with segments displaying hyperkinesia, no change, or even hypokinesia.…”
Section: Animal Models Of Takotsubo Syndromesupporting
confidence: 72%
See 1 more Smart Citation
“…However, for the study to be clinically applicable, it is crucial that global cardiac function, when used as an outcome measure, be evaluated in the context of a TS phenotype. The impact of stress inducing a reduced global systolic function, in the absence of RWMA, appears to be a recurring finding observed by us and others ( 8 , 10 , 72 ). Thus, regions with wall motion abnormalities can be associated with segments displaying hyperkinesia, no change, or even hypokinesia.…”
Section: Animal Models Of Takotsubo Syndromesupporting
confidence: 72%
“…• Mouse (16,72,(77)(78)(79)(80)(81)(82)(83)(84)(85) • Rat (11-15, 23, 86-103) • Monkey (9) • Gene-modified mouse (104) • Subarachnoid haemorrhage in rabbit (105) High dose of PDE-3 inhibitor in rat (106) Low-moderate dose of catecholamine in:…”
Section: Translational Aspectsmentioning
confidence: 99%
“…ISO is a catecholamine and causes severe myocardial necrosis. 29 , 30 The results showed in Figure 4 an increase in CK‐MB and troponin I after ISO‐induced stroke in the MI group compared with the control group. The mean serum CK‐MB activity in the control and MI groups was 86 ± 1 and 222 ± 8 IU/L, respectively, indicating a significant difference ( p < 0.0001).…”
Section: Resultsmentioning
confidence: 94%
“…ISO is a catecholamine and causes severe myocardial necrosis 29,30 . The results showed in Figure 4 an increase in CK‐MB and troponin I after ISO‐induced stroke in the MI group compared with the control group.…”
Section: Resultsmentioning
confidence: 95%
“…In the published literature, epinephrine and isoproterenol have most commonly been used to create stress-induced cardiomyopathies in animal models, we chose epinephrine because it is also used clinically to treat septic shock. [10][11][12][13] Finally, although human and animal sepsis studies have shown that large vessel coronary perfusion is not impaired during sepsis, the cardiac microcirculation has not been evaluated for impaired tissue perfusion as a cause of cardiac injury. 14,15 We previously found in our large animal model of sepsis-induced cardiac dysfunction that the coronary microcirculation is damaged, but this finding was confounded by the use of exogenous catecholamines.…”
Section: Introductionmentioning
confidence: 99%